2016
DOI: 10.1186/s13000-016-0588-x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zone lymphoma-derived interfollicular diffuse large B-cell lymphoma harboring 20q12 chromosomal deletion and missense mutation of BIRC3 gene: a case report

Abstract: BackgroundDiffuse large B-cell lymphoma (DLBCL) typically leads to effacement of the nodal architecture by an infiltrate of malignant cells. Rarely (<1%), DLBCL can present with an interfollicular pattern (DLBCL-IF) preserving the lymphoid follicles. It has been postulated that DLBCL-IF is derived from marginal zone B cells and may represent a large-cell transformation of marginal zone lymphoma (MZL), however no direct evidence has been provided to date. Here we describe a rare case of a diagnostically challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…As previously stated, HT of MZL is an extremely rare event: 3‐5% of ∼3% of all NHL implies <100 cases per annum in the US. Nevertheless, we sought to perform further cytogenetic analysis of matched cases of MZL transforming to DLBCL; including the original case reported . Remarkably, we found a significant association of del(20q12) in matched pairs of DLBCL cases transformed from NMZL, compared to an equivalent number of unmatched DLBCL cases.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As previously stated, HT of MZL is an extremely rare event: 3‐5% of ∼3% of all NHL implies <100 cases per annum in the US. Nevertheless, we sought to perform further cytogenetic analysis of matched cases of MZL transforming to DLBCL; including the original case reported . Remarkably, we found a significant association of del(20q12) in matched pairs of DLBCL cases transformed from NMZL, compared to an equivalent number of unmatched DLBCL cases.…”
Section: Introductionmentioning
confidence: 89%
“…Although rarely associated with lymphoma, del(20q12) has been reported in a case of aggressive NMZL . We recently described a case of DLBCL harboring del(20q12) in a patient with a history of MZL involving lymph nodes and skin . Polymerase chain reaction of IgG variable regions from the DLBCL and an original skin biopsy were clonally related, strongly suggesting that transformation of MZL to DLBCL had occurred.…”
Section: Introductionmentioning
confidence: 92%
“…DNA was extracted from FFPE small bowel tumor tissue and analyzed for clonality as described previously [ 11 ]. Briefly, PCR amplification was performed with two sets of fluorescently labeled primers (InVivoScribe Technologies) that hybridize to a conserved V-framework, framework 2 (FR2), and framework 3 (FR3) regions and the conserved J-region of immunoglobulin heavy chain (IGH) gene.…”
Section: Methodsmentioning
confidence: 99%
“…Mutational analysis of FFPE tissue samples was performed by the University of Pennsylvania at the Center for Personalized Diagnostics as described previously [ 11 ]. The genes sequenced were part of a custom, targeted next-generation sequencing amplicon panel testing for 68 hematologic malignancy-associated genes (ABL1, ASXL1, ATM, BCOR, BCORL1, BIRC3, BRAF, CALR, CBL, CDKN2A, CEBPA, CSF1R, CSF3R, DDX3X, DNMT3A, ETV6, EZH2, FAM5C, FBXW7, FLT3, GATA2, GNAS, HNRNPK, IDH1, IDH2, IL7R, JAK2, KIT, KLHL6, KRAS, MAP2K1, MAPK1, MIR142, MPL, MYC, MYCN, MYD88, NF1, NOTCH1, NOTCH2, NPM1, NRAS, PDGFRA, PHF6, POT1, PRPF40B, PTEN, PTPN11, RAD21, RIT1, RUNX1, SETBP1, SF1, SF3A1, SF3B1, SMC1A, SRSF2, STAG2, TBL1XR1, TET2, TP53, TPMT, U2AF1, U2AF2, WT1, XPO1, ZMYM3, and ZRSR2) (TruSeq Custom Amplicon, Illumina Inc.) based on previously described analyses [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-canonical NF-κB signaling is essential for the activation, survival and differentiation of immune cells such as B-cells, macrophages and dendritic cells. Deletion of cIAP1 and cIAP2 in mice maintained B-cells survival and maturation independent of BAFF-R stimulation [ 91 ], and can account for B-cell transformation [ 94 , 95 , 96 ]. We demonstrated that cIAP1-mediated degradation of TRAF2 is essential for the full activity of macrophages in response to CD40 stimulation [ 45 ].…”
Section: Cytoplasmic Functions Of Ciap1mentioning
confidence: 99%